Prevalence of Plasmid Mediated Quinolone Resistance Determinants among Oxyiminocephalosporin Resistant Enterobacteriaceae in Argentina. - Rincón Cruz, Giovanna (2013)
High quinolone resistance rates were observed among oxyiminocephalosporin resistant enterobacteria. In the present study, we searched for the prevalence of plasmid mediated quinolone resistance (PMQR) genes within the 55 oxyiminocephalosporin resistant enterobacteria collected in a previous survey. The main PMQR determinants were aac(6´)-Ib-cr and qnrB corresponding to 42.4% and 33.3%, respectively. aac(6?)-Ib-cr was more frequently present in CTX-M-15 producing isolates, while QnrB was homogeneously distributed in all CTX-M producers.